PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH CS6 PADA MATERI SISTEM HORMON KELAS XI SMAN 1 PARENGGEAN - Eva Tresnawati; Mukhlis Rohmadi; Ayatusa’adah Ayatusa’adah (Saintifika, 2021)
This research aims to develop learning media based on Adobe Flash CS6 on the material system of hormones that valid and practical. This research is research and development with research design model ADDIE, covering analysis, design, development, implementation, and evaluation. The instrument used a questionnaire validation is filled by media experts and material as well as a questionnaire practicality which is filled by the students. The technique of data analysis which is a technique of qualitative analysis and quantitative analysis. The results show the validation of media experts on aspects of the display of the results of 94 and aspects of programming 97, on the validation of the material to aspects of learning that is 82 and aspect of the content of 87 then the media can be said to be valid. On the questionnaire responses of students acquire 94 the media can be said to be practical.